Pengalaman Emosional Remaja dalam Kondisi Fatherless - Nadiatul Hikmah; Sri Nurhayati Selian (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
The phenomenon of fatherlessness, or the absence of a father figure, is increasingly common in modern society, particularly due to divorce, death, or the father's emotional absence from the family. This condition has the potential to impact the emotional and personality development of adolescents. This study aims to deeply understand the emotional experiences of adolescents living without a father. This study used a qualitative phenomenological approach, with data obtained through interviews, observation, and documentation of three adolescents aged 15–16 in Banda Aceh. Data analysis employed the interactive model of Miles, Huberman, and Saldana, which encompasses reduction, presentation, and conclusion drawing. The results indicate that adolescents experiencing fatherlessness not only experience social and academic impacts but also a variety of emotional impacts, ranging from withdrawal and anger to creative expression. Furthermore, fatherless adolescents rely on environmental protection and individual coping strategies. These findings demonstrate the importance of emotional family support and counseling services for orphaned adolescents to help them develop emotional balance, a positive self-concept, and resilience in facing the challenges of their psychological development.